Random and systematic errors in pairwise computer programming: a systematic review - Marín Rodríguez, William Joel (2023)
In this article, a systematic review is carried out to identify random and systematic errors in studies on computer programming in pairs in higher education students. Methodologically, we applied the fundamentals of the PRISMA statement. One thousand one hundred eighty articles were selected from the Scopus, Web of Science, and IEEE Xplore databases. After a filtering process, the final sample was 23 23 articles. The results showed that couple programming has positive effects. The existence of both random and systematic errors was observed, which questions the internal and external validity. Further research is needed to establish the benefits of couple programming more precisely.